Derivation of an improved semi-empirical expression for the re-ionisation background in low energy ion scattering spectra. (23rd September 2021) - Koslowski, H R; Linsmeier, Ch
Abstract: Low energy ion scattering is a technique to detect the energy of ions which are scattered from a surface. For noble gas ions, it is predominantly sensitive to the topmost surface layer due to strong neutralisation processes. Depending on the combination of projectile ion and target material, the scattering spectra can exhibit contributions resulting from multiple scattering processes in deeper layers when probing ions are re-ionised on the exiting trajectory. These events cause a pronounced continuum located toward lower scattering energies with respect to the direct scattering peak. In a previous work a semi-empirical formula has been given which allows fitting and derivation of quantitative information from the measured spectra [Nelson 1986 J. Vac Sci. Technol. A 4 1567-1569]. Based on the former work an improved formula is derived which has less numerical artefacts and is numerically more stable.